2018
DOI: 10.1186/s12886-018-0783-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intraocular positions of posterior implantable collamer lens by full-scale ultrasound biomicroscopy

Abstract: BackgroundTo analyze the positions of intraocular posterior Implantable Collamer Lens (ICL) and its possible relationship with vault.MethodsThis cross-sectional study included 72 patients with high myopia (134 eyes) who were followed up after phakic intraocular lens implantation. The postoperative time ranged from 1 week to 7 years. We obtained the images of ICL by using Compact Touch STS UBM and observed the position of ICL in posterior chamber and ciliary sulcus. The horizontal lines vault was measured and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
(17 reference statements)
1
45
2
Order By: Relevance
“…Garcia-Feijoo et al [ 24 ] demonstrated that ICL haptics were usually ultimately located in the ciliary sulcus or ciliary body, while Choi et al [ 25 ] demonstrated that 64.7 % of phakic IOL haptics were fixated in the ciliary sulcus. However, by analysing the full-scale UBM of 134 eyes, Zhang et al [ 26 ] found that the ICL haptics in most cases were not in the ciliary sulcus and that different haptic positions had a significant influence on postoperative vaulting. For example, the eyes with haptics on the top of the ciliary sulcus were likely to have a high vault value, while those with one haptic on the ciliary process and another haptic in the ciliary body had a low vault value.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Feijoo et al [ 24 ] demonstrated that ICL haptics were usually ultimately located in the ciliary sulcus or ciliary body, while Choi et al [ 25 ] demonstrated that 64.7 % of phakic IOL haptics were fixated in the ciliary sulcus. However, by analysing the full-scale UBM of 134 eyes, Zhang et al [ 26 ] found that the ICL haptics in most cases were not in the ciliary sulcus and that different haptic positions had a significant influence on postoperative vaulting. For example, the eyes with haptics on the top of the ciliary sulcus were likely to have a high vault value, while those with one haptic on the ciliary process and another haptic in the ciliary body had a low vault value.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis would be helpful in understanding the influence of the lens resting position in the vault. 15 , 38 Regardless of this limitation, the study reports the range of differences observed in a population with postoperative stable follow-up and using the standard technique for vault assessment. It provides information about the inter-eye variability in vault and addresses the need for further research regarding the association between vault and postoperative anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park et al [8] revealed a case with just one of four footplates located below the ciliary sulcus occurred a rotation of TICL with an angle of 11°after surgery. Zhang et al [9] considered the main reason for the dislocation of the footplate was the surgical intrinsic drawback-blindly performed underneath the iris. We hypothesize the variation of ciliary sulcus structure is a main factor infecting the position of the footplates and the subsequent rotation of the TICL.…”
Section: Discussionmentioning
confidence: 99%